Teaching How to Infer Cultural Features through the Integration of the Directed Reading Thinking Activity - Bennouioua, Hanane (Milev Journal of Research and Studies, 2021)
Language teaching is inextricably intertwined with culture teaching, and the reading skill is not exempted whereby many cultural features are pervasively encoded in literary texts. As an aftermath to the delineation of the poor level of inferential reading comprehension of first-year students of English at l’EcoleNormaleSupérieure of Sétif- MessaoudZeghar- Algeria, the instruction of the inferential comprehension of culturally laden texts through the integration of the Directed Reading Thinking Activity stimulated the aim behind the current scrutiny. To this end, a quasi-experimental pretest/posttest design constituted the methodological framework by dint of a purposeful sample selection of 34 students. Fundamental to this research was the selection of a realistic narrative entitled The Great Gatsby, which is inherently ingrained in the American culture. Ultimately, the statistical outcomes of the independent samples t-test on the performance of the posttest revealed a significant difference of p =.000 at the probability level of α<.05 in favor of the experimental group. This fact accentuated the positive effect of the treatment on the inferential reading comprehension whereby cultural schemata were omnipresent. Accordingly, diverse cultural features, that had characterized the American society in the 1920s, were inferred.